A ROMANIAN PERSPECTIVE ON DETERMINING THE COMPETENT COURT FOR THE SHARING-OUT OF THE ESTATE IN THE LIGHT OF REGULATION (EU) NO. 650/2012 - Silviu-Dorin ŞCHIOPU (Challenges of the Knowledge Society)
The Treaty on the Functioning of the European Union provides that the Union shall develop judicial cooperation in civil matters having cross-border implications and, for this purpose, the European Parliament and the Council shall adopt measures for the proper functioning of the internal market, aimed at ensuring the compatibility of the rules applicable in the Member States concerning conflict of laws and of jurisdiction. To this end, the European Parliament and the Council of the European Union have adopted Regulation (EU) no. 650/2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of succession and on the creation of a European Certificate of Succession, which applies to successions of natural persons who died on or after 17 August 2015. There are more than a few cases in which the increasing mobility of private individuals, in particular within the European Union, gives rise to matters of succession with cross-border implications, such as when the deceased was the national of a state other than the state of their habitual residence at the time of death or when the assets forming part of the estate are located in the territory of several states. Thus, the inheritance, including the sharing-out of the estate, may fall under the scope of several legal systems. Under such circumstances, in the case of a judicial sharing-out of the estate, we are dealing with a private law matter having cross-border implications, which could result in a conflict of law, within the meaning that the dispute could be settled by courts from several states. In light of the above, this short overview aims to analyse, on the one hand, the rules applicable in order to determine the court or courts of law competent to settle the sharing out of the estate, or the international jurisdiction of Romanian courts over foreign ones, without overlooking the correlation between the jurisdiction and the law applicable to the succession as a whole. After determining the state the courts of law of which hold jurisdiction, we will refer to internal jurisdiction, both in territorial and substantive terms, in line with the rules of the domestic civil procedural law. One of the conclusions of our overview is that, although the regulation aims to ensure that the court of law ruling in connection with the sharing-out of the estate will enforce, in most of the cases, its own law, in practice, there will also be instances where the rules of procedural law will pertain to the legal system of one Member State which was party to the adoption of the Regulation, while the rules of substantive law will pertain to a third country. Thus, it is not impossible for the Romanian courts of law to enforce rules of substantive law pertaining to another legal system, all the more as, in accordance with Article 23 paragraph (2) letter j) of Regulation (EU) no. 650/2012, the scope of the applicable law also encompasses the sharing-out of the estate.